2009
DOI: 10.1007/s11433-009-0243-6
|View full text |Cite
|
Sign up to set email alerts
|

The calibration and initial results of the HeI D3 line flash spectrum obtained during the 2008 total solar eclipse

Abstract: The flash spectra in the HeI D3 line were obtained during the 2008 total solar eclipse. This paper describes the instrument and the calibration of the obtained flash spectrum, and presents our initial results. The average integrated intensity is Eave = 8.13×10 13 erg·cm −1 · s −1 ·ster −1 at h = 1100 km, which confirms that the HeI D3 emission is negatively correlated with the solar activity. The surface brightness reaches a maximum of F ave = 8.25×10 5 erg·cm −2 ·s −1 ·ster −1 at about h ≈ (1290 ± 75) km and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…By inspecting the central eclipse video records, he retrieved the data for the time when the Baily beads appeared, and deduced the value for the solar radius. Li et al [28] obtained the flash spectra in the He I D3 line during the 2008 total solar eclipse. The initial results of their observations confirmed that the He I D3 emission is negatively correlated with the solar activity.…”
Section: The Total Eclipse and Its Observationsmentioning
confidence: 99%
“…By inspecting the central eclipse video records, he retrieved the data for the time when the Baily beads appeared, and deduced the value for the solar radius. Li et al [28] obtained the flash spectra in the He I D3 line during the 2008 total solar eclipse. The initial results of their observations confirmed that the He I D3 emission is negatively correlated with the solar activity.…”
Section: The Total Eclipse and Its Observationsmentioning
confidence: 99%
“…Flash spectra are known for a long time [1] . Recently, observations of flash spectra were carried out by different observers at total solar eclipses using a CCD camera [2] and flash spectra experiments using optical fibers were made for polarization analysis [3] . During our observations, we performed a high cadence CCD slitless spectra in the region of the neutral helium He I 4713 Å line and of the ionized helium He II 4686 Å line, with the aim of studying the top of the photosphere and the chromosphere to corona transition region [4] .…”
Section: Introductionmentioning
confidence: 99%
“…Observations at total solar eclipses have their advantages for scientific studies though lots of space-borne observatories are working [10,11]. At the total solar eclipse on August 1, 2008, several groups organized by the Chinese Academy of Sciences carried out scientific observations in Jiuquan, Gansu Province, and obtained many observational results [12][13][14][15][16][17]. Those results are related to many subjects of solar physics, such as the spectra and polarizations of the solar chromosphere and corona, and the fine structures of corona.…”
Section: Introductionmentioning
confidence: 99%